The effect of nitric oxide on the pyrolysis of ethane. - Esser, Joseph. (University of Ottawa (Canada), 1969)
The pyrolysis of ethane inhibited by nitric oxide has been investigated at temperatures ranging from 550 to 596°C by gas-chromatographic analysis. Mixtures of C2H6-NO ranged from 1.6 to 62% NO. The rates of production of the primary products ethylene, hydrogen, methane, nitrogen, water, nitrous oxide and acetonitrile were measured under varying experimental conditions. Hydrogen cyanide, carbon monoxide, acetaldehyde, n-butane, butene-1, cis- and trans-butene-2, and butadiene-1,3 were detected as secondary products and occasionally measured. It was found that nitric oxide decomposed extensively with a finite initial rate. The consumption of NO was determined directly and a good mass balance was obtained. The orders of the rates of formation with respect to ethane and nitric oxide were determined for all primary products at 596°C. The activation energies for the production of all primary products were determined for two different C2H6-NO mixtures in the temperature range 550 to 596°C. Except for t he production of water and nitrogen the activation energies were found to depend on the composition of the mixture. A mechanism is proposed which gives good agreement with experiment. The main points of the mechanism are: (i) Initiation takes place mainly by unimolecular decomposition of ethane. (ii) Nitric oxide scavenges ethyl radicals to form acetaldoxime which decomposes, thereby replacing in essence the reaction C2H5→C2 H4+H to a large extent by C2H5+NO→C2H 4N+OH. In this way the C2H5 radical causes the decomposition of nitric oxide. (iii) Termination takes place mainly by unimolecular decomposition of acetaldoxime to inactive products. Reactions are proposed to account for the formation of the secondary products observed. Some of the relevant rate parameters are evaluated. An interpretation is given of the rate measurements previously performed by means of pressure measurements.
Keywords: Chemistry, Organic.